History and methodology of science study aid - Skakovskaya, N. V. philosopher Associate Professor of Tomsk Polytechnic University, Candidate of Philosophical Sciences 1980- (TPU Publishing House, 2021)
The textbook represents the short review of questions which are studied by philosophy of science. The basic attention is given history of scientific thought, the major scientific and philosophical concepts, and as to the problems connected with influence of a science on all life. The study aid is developed for all master's degree of the TPU.